ANALISIS KETERKAITAN DAN DAMPAK SEKTOR PERDAGANGAN DAN INDUSTRI TERHADAP PDRB JAWA TIMUR - YOALINA S.N.A (Universitas Negeri Surabaya, 2014)
East Java Province is the second biggest contributor of Indonesia Gross Domestic Product (GDP) after Jakarta. Furthermore, trade and industry sectors were the major contributors of East Java Province’s GDP in 2010. The high level of trade and industry sectors contribution on East Java Province’s GDP caused by linkage between trade and industry sectors and other sectors. So, this research’s aim is to dig the linkage between those two sectors and their influences towards the economic condition of East Java Province by using Input-Output analysis method. According to the tabulation data, the backward linkage of industry sector was 1,604, while the trade sector was 1,204. The backward linkage of industry and trade sectors were included in the high category. It also occured on the forward linkage of industry and trade sectors, with the amount was 1,345 and 1,579, included in the category of high linkage. Meanwhile, according to the number of output, income, and labor multiplier, which were 1,604, 0,133, 6,235, the industry sector obviously had a big influence towards the output of East Java Province economy. However, it only effected slightly towards the increase of people income and vocation. On the other hand, the number of output, income, and labor multiplier of the trade sector, which were 1,204, 0,284, and 19,710, showed its significant influence towards the output produced, the increase of people income and vocation in East Java Province. This research suggest to be more concern towards each sector potential and ability in order to increase the economic of East Java Province optimally. Keywords : Input-Output Analysis, Trade Sector, Industry Sector, Linkage, Multiplier Jawa Timur merupakan salah satu provinsi penyumbang PDB nasional terbesar kedua setelah DKI Jakarta. Sektor perdagangan dan industri merupakan sektor penyumbang utama dalam PDRB Jawa Timur tahun 2010. Tingginya kontribusi sektor perdagangan dan industri tersebut dikarenakan adanya hubungan saling terkait sektor perdagangan dan industri dengan sektor-sektor yang lain. Sehingga penelitian ini bertujuan untuk mengetahui keterkaitan kedua sektor tersebut dan dampaknya terhadap perekonomian Jawa Timur dengan menggunakan analisis Input-Output. Berdasarkan hasil pengolahan data, keterkaitan ke belakang sektor industri adalah sebesar 1,604 dan sektor perdagangan sebesar 1,204. Keterkaitan ke belakang sektor industri dan perdagangan tersebut termasuk dalam kategori tinggi. Demikian pula dengan keterkaitan ke depan sektor industri dan perdagangan yaitu sebesar 1,345 dan 1,579 yang juga termasuk dalam kategori keterkaitan tinggi. Sedangkan, berdasarkan angka pengganda output, pendapatan, dan tenaga kerjanya, yaitu sebesar 1,604, 0,133, 6,235, sektor industri memiliki dampak yang besar dalam output yang dihasilkan dalam perekonomian Jawa Timur. Namun, sektor industri memiliki dampak yang kecil terhadap peningkatan pendapatan masyarakat dan penyerapan tenaga kerja. Di sisi lain, angka pengganda output, pendapatan, dan tenaga kerja sektor perdagangan, yaitu 1,204, 0,284, dan 19,710, menunjukkan adanya dampak yang besar terhadap output yang dihasilkan, peningkatan pendapatan masyarakat, dan penyerapan tenaga kerja di Jawa Timur. Penelitian ini menyarankan untuk lebih memperhatikan potensi dan kemampuan masing-masing sektor sehingga perekonomian Jawa Timur dapat berkembang secara optimal. Kata Kunci : Analisis Input-Output, Sektor Perdagangan, Sektor Industri, Keterkaitan, Pengganda.